Artificial Intelligence in Product Visual Representation within Islamic Business: A Conceptual Analysis Based on Maqashid Shariah - Andini Asmarini (Yayasan Azhar Amanaa Yogyakarta, 2025)
The advancement of Artificial Intelligence (AI), particularly Generative AI, has transformed digital marketing by enabling businesses to create attractive product visual representations efficiently. However, AI-generated images may misrepresent the actual characteristics of products, potentially leading to tadlis (misrepresentation) and gharar(uncertainty) in Islamic business transactions. This study aims to analyze the use of AI in product visual representation from the perspective of maqashid shariah and formulate normative parameters for its ethical application. This research employs a library research method with a conceptual approach. Data were collected from scholarly articles, books, regulations, fatwas, and other relevant literature, and analyzed using descriptive content analysis. The findings indicate that AI is permissible as a technological tool (wasilah) provided that its use does not mislead consumers. From the perspective of maqashid shariah, AI should protect wealth (hifz al-mal) and intellect (hifz al-'aql) by ensuring accurate, transparent, and accountable product representation. This study proposes five normative principles for AI-based product visualization: representational accuracy, transparency, consumer protection, accountability, and maslahah orientation.